Synthesis of structured ether lipids and n-3 polyunsaturated fatty acids - Edda Katrín Rögnvaldsdóttir 1987- (2013)
Ether lipids of the 1-O-alkyl-2,3-diacyl-sn-glycerol type, made of pure saturated or monounsaturated 1-O-alkyl-sn¬-glycerols and long chain n-3 polyunsaturated fatty acids (PUFAs), are interesting compounds since their parts are thought of as biologically active. Twelve different types 1-O-alkyl-2,3-diacyl-sn-glycerols can be made by using enantiopure chimyl (16:0), batyl (18:0) and selachyl (18:1) alcohols and two different PUFAs, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), in the sn-2 and sn-3 positions. In the first part of the synthesis an immobilized Candida antarctica lipase (CAL) was used for the acylation of the primary hydroxyl group at the end position, using an acetoxime ester of the corresponding PUFA. Then in the second part, the mid position was esterified, with the same or the other PUFA, with chemical acylation using EDAC as a coupling agent. The n-3 polyunsaturated fatty acids α-linolenic acid (ALA) and docosapentaenoic acid (DPA) are likewise interesting compounds. They have various biological effects and partake in many different biological pathways. In their total synthesis, the PUFAs were constructed in two parts that were then coupled together. Part one consisted of the synthesis of the polyyne tails, which were made through a series of copper mediated coupling reactions. Part two involved the protection of the carboxyl acid group, followed by an alkylation which formed a terminal acetylene. The two parts were then combined with a coupling reaction, followed by partial hydrogenation used to gain the cis-configuration of the double bonds, and then the protection group was removed to afford the ALA and DPA, respectively. Eterlípíð af 1-O-alkýl-2,3-diasyl-sn-glýseról-gerð, sem eru samansett úr mettuðum eða einómettuðum 1-O-alkýl-sn¬-glýserólum og löngum n-3 fjölómettuðum fitusýrum (PUFA), eru áhugaverð efni þar sem allir hlutar þeirra eru taldir hafa líffræðilega virkni. Mynda má tólf mismunandi gerðir 1-O-alkýl-2,3-díasyl-sn-glýseróla með handhverfuhreinum kimýl- (16:0), ...